Pengaruh Penggunaan Podcast Youtube Podcastacular Terhadap Minat Belajar Siswa - Elriyo Rizki Athaya; Christian Arief Jaya (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of using the YouTube podcast Podcastacular on students' learning interest at SMA Negeri 3 Semarang. The study used a quantitative approach with a pre-experimental design in the form of a One Group Pretest–Posttest Design. The research subjects were 36 grade XII students selected using a saturated sampling technique. Data collection was carried out through a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used a normality test to determine the distribution of the data, a paired sample t-test to test the difference in the average pretest and posttest scores on normally distributed data, and a Wilcoxon test as a nonparametric test to strengthen the results of the data difference test. The results showed that the data were normally distributed with a significance value > 0.05. The results of the paired sample t-test obtained a significance value of 0.019 (<0.05), while the Wilcoxon test obtained a significance value of 0.025 (<0.05), which indicated a significant difference between the pretest and posttest scores. However, descriptively, the average learning interest after treatment (29.16) was lower than before treatment (31.11). This finding indicates that podcast use influences students' learning interest, but has not yet provided optimal positive improvements.